Dynamic modeling of native vegetation in the Piracicaba River basin and its effects on ecosystem services - Molin, Paulo Guilherme (2014)
Studies from the Forestry Institute of São Paulo State have shown that in the end of the 20th century, the native forest cover of the state of SP reached the maximum level of forest loss. From that point on, a period of forest increase and expansion started. Industrialization, law enforcement, economic benefits, and social pressure experienced in recent years are believed to be contributing to the preservation and regrowth of the native vegetation cover in certain locations. This study proposed to model the dynamics of native vegetation cover in the Piracicaba River basin (12,500 km²) in the state of São Paulo, Brazil, to evaluate possible effects of these changes in ecosystem services related to river flow & regulation and landscape structure, linking to biodiversity & habitat supported by forest patches. To achieve the proposal set out in this research, dynamic models of native vegetation were established. Thematic land cover maps of the years 1990, 2000 and 2010, originated from Landsat 5 TM images, formed the spatiotemporal basis of this study. With the aid of Dinamica EGO (a dynamic modeling software), three future scenarios were created, called status quo (SQ), no deforestation (ND) and riparian restoration enforcement (RRE). An analysis using weights of evidence was done to identify forest transition drivers. The drivers are divided into two groups, (1) environmental & physical, consisting of soil types, hydrographic network, rainfall and presence of native forest fragments and (2) anthropic, consisting of population density, gross national product, road network, urban patches and predominant rural activities. Resulting scenarios were analyzed by means of landscape metrics to compare and qualify vegetation patches in relation to structure as proxy for supporting ecosystem services. Finally, Soil & Water Assessment Tool (SWAT), a hydrological model, was used to determine the influence of different forest scenarios in mean annual water yield and regulation processes throughout the basin, and, therefore, compare scenarios as to effects on regulating ecosystem services. Results show that forest transition is indeed occurring, with native vegetation cover parting from 24.4% in 1990, to 20.1% in 2000 and 21.8% in 2010. Scenario results were of 22.4% (SQ), 43.2% (ND) and 28.4% (RRE) for 2050. Forest loss was identified as a product of anthropogenic drivers while regrowth was of physical & environmental drivers. When the area was segmented, regions with greater environmental condition resulted in improved values of landscape structure. SQ scenario was the most affected, losing small patches of forest that could function as structural connectors, and therefore potentially affect biodiversity and habitat. Mean annual water yield was reduced with forest regrowth by as much as 10.3% in ND. We concluded that the dynamics occurring in the landscape and the proposed scenarios affect mean annual water yield, regulation and landscape structure, allowing us to discuss differences between the scenarios and the relation between forest dynamics, landscape structure, hydrology and overtime potential effects over regulating and supporting ecosystem services.